2015
DOI: 10.4028/www.scientific.net/amr.1119.622
|View full text |Cite
|
Sign up to set email alerts
|

Surface Roughness Analysis of Carbon/Glass Hybrid Polymer Composites in Drilling Process Based on Taguchi and Response Surface Methodology

Abstract: Drilling is an essential secondary process for near net-shape of hybrid composite as to achieve the required dimensional tolerances prior to final application. Dimensional tolerance is often influenced by the surface integrity or surface roughness of the workpart. Thus, this paper aims to employ the Taguchi and response surface methodologies in minimizing the surface roughness of drilled carbon-glass hybrid fibre reinforced polymer (CGCG) using tungsten carbide, K20 drill bits. The effects of spindle speed, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…(ii) The increase in drill speed may also result in cutting of fibers owing to the absences of drill tool bouncing and softening of matrix martial which may results in lower order of responses. (iii) The wide range of thrust force (40-85 N) and torque (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) was observed with HSS drill material for the tested limits of spindle speed (500-2500 r/min) and feed rate (0.05-0.25 mm/r). But SC drill material showed marginal variations initially due to its high hardness, high stiffness, and keenness of cutting edge.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…(ii) The increase in drill speed may also result in cutting of fibers owing to the absences of drill tool bouncing and softening of matrix martial which may results in lower order of responses. (iii) The wide range of thrust force (40-85 N) and torque (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) was observed with HSS drill material for the tested limits of spindle speed (500-2500 r/min) and feed rate (0.05-0.25 mm/r). But SC drill material showed marginal variations initially due to its high hardness, high stiffness, and keenness of cutting edge.…”
Section: Discussionmentioning
confidence: 94%
“…Basavarajappa et al 26 have developed the RSM model for quantifying the process responses with essential input parameters. Tan et al 27 have formulated the regression model using RSM to forecast process responses in drilling of CF/GF hybrid composite material and they have concluded that the quality of drilled holes is highly affected by drill geometry and feed rate. Rajmohan and Palanikumar 28 have developed a model and optimized the drilling process parameters through RSM-based D-optimal design.…”
Section: Introductionmentioning
confidence: 99%
“…9, the last layer have been a fiber layer, that means two layers were separated from the base square. As seen in table (6) and 7, SN ratios and ANOVA tables, showed results of the significant factors, F-value and P-value and contribution of each parameter. Feed rate is the most significant factor by 70%, while spindle speed affects the lowest by 6%.…”
Section: A Fiberglass-aluminum With Epoxy Resin Compositementioning
confidence: 95%
“…Tan et al [6] the author in his research used woven carbon fibers, woven E-glass fibers, in EpoxAmite matrix and hardener resin as the materials. The direction of woven carbon (C) and glass (G) fibers were organized in the grouping of [CGCG] these fibers were stacked in the glass mold until thickness 4 mm has been accomplished and they were fixed and compacted with vacuum sack under a vacuum from 11 to 15mBar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation